Primera cita de Aleiodes laphygmae (Hym.: Braconidae) para Argentina y de su asociación con larvas de S. eridania (Lep.: Noctuidae) - Valverde, Liliana (2012)
Aleiodes laphygmae (Viereck) (Hymenoptera: Braconidae), is reported for the first time in Argentina and parasitizing larvae of Spodoptera eridania (Stoll) (Lepidoptera: Noctuidae) in soybeans crops in Tucumán province (Argentina). Biological information, as habits, hosts and distribution are provided.